UJI BAKTERI Escherichia coli PADA AIR SUNGAI PIAM DI KECAMATAN SIRAPIT KABUPATEN LANGKAT - Ari Anggara (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2020)
This study aims to determine the presence of Escherichia coli bacterial contamination in Piam River Water. The method used in this study is to use the Purpose Sampling observation method with three station points and three replications and the results are read in the MPN table. The results showed that the presence of Escherichia coli bacterial contamination in Piam River water with the lowest MPN yield was 38 CFU and the highest was 1100 CFU. The average MPN value on Escherichia coli bacterial contamination at station 1 in the morning was 59 CFU and afternoon was 111 CFU. Station 2 in the morning 128 CFU and afternoon 303 CFU. And at station 3 in the morning 92 CFU and afternoon 886 CFU.